Validation of a single‐stage fixed‐rate step test for the prediction of maximal oxygen uptake in healthy adults. (5th June 2015) - Hansen, Dominique; Jacobs, Nele; Thijs, Herbert; Dendale, Paul; Claes, Neree
Summary: Healthcare professionals with limited access to ergospirometry remain in need of valid and simple submaximal exercise tests to predict maximal oxygen uptake (VO2max ). Despite previous validation studies concerning fixed‐rate step tests, accurate equations for the estimation of VO2max remain to be formulated from a large sample of healthy adults between age 18–75 years ( n  > 100). The aim of this study was to develop a valid equation to estimate VO2max from a fixed‐rate step test in a larger sample of healthy adults. A maximal ergospirometry test, with assessment of cardiopulmonary parameters and VO2max, and a 5‐min fixed‐rate single‐stage step test were executed in 112 healthy adults (age 18–75 years). During the step test and subsequent recovery, heart rate was monitored continuously. By linear regression analysis, an equation to predict VO2max from the step test was formulated. This equation was assessed for level of agreement by displaying Bland–Altman plots and calculation of intraclass correlations with measured VO2max . Validity further was assessed by employing a Jackknife procedure. The linear regression analysis generated the following equation to predict VO2max (l min −1 ) from the step test: 0·054(BMI)+0·612(gender)+3·359(body height in m)+0·019(fitness index)−0·012(HRmax)−0·011(age)−3·475. This equation explained 78% of the variance in measured VO2max ( F  = 66·15, P <0·001). The level of agreement and intraclass correlation was high (ICC = 0·94, P <0·001) between measured and predicted VO2max . From this study, a valid fixed‐rate single‐stage step test equation has been developed to estimate VO2max in healthy adults. This tool could be employed by healthcare professionals with limited access to ergospirometry.